2017
DOI: 10.1159/000481867
|View full text |Cite
|
Sign up to set email alerts
|

ICS Use May Modify FEV<sub>1</sub> Decline in α<sub>1</sub>-Antitrypsin Deficiency Patients with Relatively High Blood Eosinophils

Abstract: Background: α 1 -Antitrypsin deficiency (AATD) predisposes to chronic obstructive pulmonary disease (COPD). In COPD unrelated to AATD, the role of a higher blood eosinophil count in disease and subsequent personalization of therapy has recently received much attention. We sought to investigate this concept in patients with AATD-associated COPD. Objectives: The study aims to evaluate eosinophilia status against outcomes including mortality and FEV 1 decline in patients with AATD. Methods: All patients with PiSZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Inhaled therapies are prescribed according to the degree of breathlessness and inhaled corticosteroids have been shown to reduce FEV1 decline in PiZZ AATD patients with persistent eosinophilia. 56…”
Section: Inhaled Therapiesmentioning
confidence: 99%
“…Inhaled therapies are prescribed according to the degree of breathlessness and inhaled corticosteroids have been shown to reduce FEV1 decline in PiZZ AATD patients with persistent eosinophilia. 56…”
Section: Inhaled Therapiesmentioning
confidence: 99%
“…In one large study, implementation of a management plan associated with increased adherence to pharmacological therapy was shown to reduce exacerbations and unscheduled healthcare use and improve health‐related quality of life . A post hoc analysis of another study suggested that inhaled corticosteroid could be useful in patients with AATD‐associated COPD who have persistent peripheral blood eosinophilia . Prescription of inhaled therapy, oxygen and treatment of exacerbations in AATD should be considered using similar principles to other patients with COPD …”
Section: Management Of Aatd (Other Than Augmentation Therapy and Surgmentioning
confidence: 99%
“…105 A post hoc analysis of another study suggested that inhaled corticosteroid could be useful in patients with AATDassociated COPD who have persistent peripheral blood eosinophilia. 106 Prescription of inhaled therapy, oxygen and treatment of exacerbations in AATD should be considered using similar principles to other patients with COPD. [94][95][96] Extrapulmonary manifestations: Management of liver complications AATD causes chronic hepatitis and its sequelae including liver fibrosis, cirrhosis and hepatocellular carcinoma.…”
Section: Pharmacological Managementmentioning
confidence: 99%
“…ICS can reduce the FEV 1 decline in patients with higher blood eosinophils counts at baseline. 51 Although many previous studies have demonstrated the value of inflammatory markers in ACO diagnosis, [15][16][17][18][19] the results remain highly controversial. 20 Kobayashi et al 15 found that 156.2/mm 3 was the best diagnostic cut-off level of EOS for ACO diagnosis, with the sensitivity and specificity being 49.5% and 83.8%, respectively.…”
mentioning
confidence: 99%